HBR guide to project management - Sheen, Raymond; Gallo, Amy (Harvard Business review guides, 2022)
MEET YOUR GOALS-ON TIME AND ON BUDGET. How do you rein in the scope of your project when you've got a group of demanding stakeholders breathing down your neck? And map out a schedule everyone can stick to? And motivate team members who have competing demands on their time and attention? Whether you're managing your first project or just tired of improvising, this guide will give you the tools and confidence you need to define smart goals, meet them, and capture lessons learned so future projects go even more smoothly. The HBR Guide to Project Management will help you: build a strong, focused team; break major objectives into manageable tasks; create a schedule that keeps all the moving parts under control; monitor progress toward your goals; manage stakeholders' expectations; and wrap up your project and gauge its success.